Modelling of entrepreneurial leadership for effectiveness of schools - Dahiru, Abbas Sani; Lope Pihie, Zaidatol Akmaliah (International Digital Organization for Scientific Information, 2016)
Entrepreneurial leadership practice is an exclusive leadership practice that aid in confronting the tasks and challenges of organizations. However many questions had been raised on the influence of the leadership style in the educational settings. This paper explained the concepts of entrepreneurial leadership, school effectiveness, dimensions of entrepreneurial leadership, the role of entrepreneurial leadership in achieving school effectiveness. And finally the implications of the paper to the body of knowledge, policy makers and school principals were discussed in the paper.